2015
DOI: 10.1016/j.cyto.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of acute phase reactants Interleukin-6, C-Reactive Protein and Procalcitonin as biomarkers of intra-amniotic infection and chorioamnionitis

Abstract: Background The arsenal of maternal and amniotic fluid (AF) immune response to local or systemic infection includes among others the acute-phase reactants IL-6, C-reactive protein (CRP) and procalcitonin (PCT). If these molecules can be used as non-invasive biomarkers of intra-amniotic infection (IAI) in the subclinical phase of the disease remains incompletely known. Methods We used time-matched maternal serum, urine and AF from 100 pregnant women who had an amniocentesis to rule out IAI in the setting of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 37 publications
3
54
1
4
Order By: Relevance
“…There are few references exploring the maternal blood compartment in women with available information on amniotic fluid and although some authors [45,46] have reported higher levels of some acute inflammatory biomarkers, such as IL-6 and C-reactive protein, in maternal blood, the observed inflammatory response was too weak to be taken into consideration in clinical practice. …”
Section: Maternal Bloodmentioning
confidence: 99%
“…There are few references exploring the maternal blood compartment in women with available information on amniotic fluid and although some authors [45,46] have reported higher levels of some acute inflammatory biomarkers, such as IL-6 and C-reactive protein, in maternal blood, the observed inflammatory response was too weak to be taken into consideration in clinical practice. …”
Section: Maternal Bloodmentioning
confidence: 99%
“…So far, the validation of Hp&HpRP as a biomarker of antenatal exposure to IAI has only been performed in CB available at birth, a time frame which is far too late for clinical decisions by physicians. A previous study by Dulay et al [28] showed that the compartmentalization process characteristic to human pregnancy is a significant obstacle to using levels of maternal blood or urine inflammatory cytokines to infer information on the same analytes in AF or CB (fetal) compartment. Although the study by Dulay et al [28] did not include the evaluation of Hp&HpRP as a biomarker, it is known that maternal blood Hp&HpRP expression or levels are clinically irrelevant in this context, since Hp is normally expressed in the adult at high levels [14,15] .…”
Section: Discussionmentioning
confidence: 99%
“…İnflamatuar belirteçlerin preterm doğumların öngörüsünde kullanılabileceği iddia edilmiştir. 134,135 Enfeksiyonun bir akut faz reaktanı olan CRP, hızlı artan ve yarılanma süresi kısa olan, hepatositlerden sentezlenen bir proteindir. İnflamasyon ve doku hasarını yansıtan CRP, non invaziv, çabuk sonuç alınan, ucuz ve kolay ulaşılabilir bir testtir.…”
Section: Akut Faz Reaktanlarıunclassified
“…Preterm eylem nedeni ile izlenen gebelerde CRP artışının, amniyotik sıvı enfeksiyonunu ve ilk hafta içinde preterm doğum riskini öngördüğü bildirilmiştir. [134][135][136] Salih ÇETİNKAYA ve ark.…”
Section: Akut Faz Reaktanlarıunclassified
See 1 more Smart Citation